KRISTEN-BARAT MEMBANGUN KERUKUNAN - Harda Armayanto (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
Discussion about harmony can not be separated from the discussion of plurality. Plurality or diversity is a fact that must be faced for all communities and reigious people. Each religion has its own experience and the typical way in addressing the plurality. Western Christian society also have a typical story in the face of plurality around them. Cruelty that came from the Church, caused and affected their own experience of looking at something, as well as looking at the plurality and harmony. Surprisingly, this Western worldview plagiarized by the liberal Muslims. Finally, the concepts of harmony in Islam that should be tawhidi based on al-Quran and al-Sunnah turned into a secular by ruling out both. This article explores the stages through by the Western Christian societies in responding the plurality to build harmony. It is important to be clear how the Muslim community should be, whether to follow the ways of the or to explore directly the basic sources of religion, al-Quran and al-Hadith.